(untitled) (Biosaintifika: Journal of Biology & Biology Education, 2024)
Gyrinops versteegii tends to grow naturally in the western region of Lombok Island, while cultivated G. versteegii tends to spread over the eastern region. These two distribution patterns cause different characteristics of this species that can be excellent sources for genetic population study including genetic diversity and population inbreeding. This research aims to conduct a genetic population analysis of G. versteegii from western and eastern agarwood distribution on Lombok Island using the RAPD marker. G versteegii samples were taken from west region (8o 31ʹ 26ʺ S, 116o 07ʹ 03ʺ E) and east region (8o 42ʹ 28ʺ S, 116o 27ʹ 11ʺ E). RAPD PCR of genomic DNA was conducted using primers: OPA-01, OPA-02, OPA-04, OPA-08, OPA-09, and OPA-18. Genetic population analysis (allele frequencies, heterozygosity, Shannon index, band pattern, and AMOVA) was performed by GenAlEx 6.5. OPA-02 has an ideal discriminative power based on the number of alleles per locus and the Shannon information index. Observed heterozygosity was higher than expected heterozygosity in both the west and east populations of G. versteegii. Based on banding pattern analysis, the eastern population has higher genetic diversity than the western population. AMOVA has shown that molecular variation within the population was higher than molecular variation among the population. It could be concluded that the west and east populations of G. versteegii have a particular genetic variation that could be discriminated by RAPD primer. Despite the genetic diversity, inbreeding between those two populations has occurred constantly. This result could give new insight into the gene flow between two G. versteegi populations, which could support the development of this commodity.